2020
DOI: 10.1371/journal.pone.0237791
|View full text |Cite
|
Sign up to set email alerts
|

The lack of K13-propeller mutations associated with artemisinin resistance in Plasmodium falciparum in Democratic Republic of Congo (DRC)

Abstract: Artemisinin-based combination therapies (ACTs) have been recommended by the World Health Organization (WHO) as first-line treatment of uncomplicated Plasmodium falciparum (P. falciparum) malaria since 2005 in Democratic Republic of Congo (DRC) and a regular surveillance of the ACT efficacy is required to ensure the treatment effectiveness. Mutations in the propeller domain of the pfk13 gene were identified as molecular markers of artemisinin resistance (ART-R). This study investigated the pfk13-propeller gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Samples with PCR-confirmed presence of P. falciparum were used to amplify segments of interest on pfk13 and pfcrt genes. The procedures previously described were used to amplify the interest segment on pfcrt gene [ 25 ] and that on the propeller region of pfk13 gene [ 23 ]. The analysis of P. falciparum genes polymorphisms was done by DNA bi-directional sequencing using Sanger method as previously described [ 15 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples with PCR-confirmed presence of P. falciparum were used to amplify segments of interest on pfk13 and pfcrt genes. The procedures previously described were used to amplify the interest segment on pfcrt gene [ 25 ] and that on the propeller region of pfk13 gene [ 23 ]. The analysis of P. falciparum genes polymorphisms was done by DNA bi-directional sequencing using Sanger method as previously described [ 15 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…To help improve long-term monitoring of anti-malarial drug resistance, the present study aimed to provide baseline data for biennial molecular surveillance of P. falciparum anti-malarial drug resistance by comparing data from the study conducted in 2019 to previously published data from a similar study conducted in 2017 in the DRC [ 15 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although none of the mutations associated with ART resistance in Southeast Asia have been found in this study, 7 coding substitutions that are of unknown phenotype were observed, among which 3 have been previously reported, notably N498I in Kenya [21], N554K in Comoros and A557S in Togo and DRC [22], and 4 others that had not yet been reported (F506L, E507V, D516E, G538S). Numerous pfk13-propeller mutations of unknown function are commonly reported in sub-Saharan African countries, including the DRC [18,22,23]. There are criteria for prioritizing further laboratory studies, notably the frequent observation of a new allele with a non-synonymous mutation, the evidence of dissemination and preliminary association with clinical data whenever possible [23].…”
Section: Discussionmentioning
confidence: 99%
“…The target sequence was a 506-nucleotide fragment of the pfk13-propeller gene covering codon-positions 427-595, following a procedure previously described [18]. This segment of interest includes mutations associated with ART resistance [7].…”
Section: Pfk13 and Pfcrt Genes Polymorphismsmentioning
confidence: 99%
“…In isolated cases, reduced cell susceptibility to a drug against a metabolic enzyme occurs by mutations in the enzyme itself (Dicker et al, 1993;Wilson et al, 1992;Yun et al, 2008). However, the myriad of pathways employed by cells to counter susceptibility to drugs, including efflux and rewiring of metabolic pathways, is astounding (Aouida et al, 2004;Barrett et al, 2011;Chang et al, 2019;Chitanga et al, 2011;Claus et al, 2014;Dermawan et al, 2014;Gatti et al, 2015;Haider et al, 2020;Seyhan et al, 2012;Yobi et al, 2020;Zhang et al, 2019b). For these reasons, it is prudent to delay conclusions that genes identified by sequencing of genomes from drug-resistant cells are targets of the drugs until confirmatory data from other studies are obtained.…”
Section: Unbiased Strategies For Discovery Of Drug-binding Proteins In Cellsmentioning
confidence: 99%